(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This article examines the current trade war between the United States and China. The practical benefit of the trade war for both China and the United States is discussed, and it can be concluded that a war between the two countries, which constitute 40% of the global economy, will not achieve the results that Americans desire and can be avoided by resolving the imbalances. Structural trade and permanent and effective strategic communications, although a trade war could significantly reduce or eliminate the current account deficit of the United States. The capital account can move the current account, and capital account surpluses persist in the United States due to the country’s vast capital markets and excess foreign savings inflows. It is almost impossible to hinder China’s technological progress. Developing technology could increase China’s overall output, especially the wages of skilled workers, which is essential to China’s consumption-driven economy and is much needed. This, in turn, is extremely important for reducing China’s excess savings. The Chinese government has the determination and ability to develop technology. It is worth noting that stifling China’s technological progress is likely to harm the goal of trade rebalancing. The American goals of fixing the trade imbalance and stopping technological progress in China will pose a great challenge because they are counterproductive. The trade war is certainly hitting the weak Chinese economy. In order to fix the trade imbalance and end and avoid war, China must intensify economic reforms. . In the short term, it must work to prevent further devaluation of the Chinese currency and raise interest rates. The United States may need to reduce capital account surpluses by allowing and encouraging foreign central banks to accumulate a synthetic currency in place of the US dollar. It is also necessary for both countries to return to the negotiating table. Both countries must convey their "final line" accurately and interpret each other’s signals correctly.